Association of Left Atrial Booster‐Pump Function with Heart Failure Symptoms in Patients with Severe Aortic Stenosis and Preserved Left Ventricular Ejection Fraction. Issue 5 (18th September 2014) - Imanishi, Junichi; Tanaka, Hidekazu; Sawa, Takuma; Motoji, Yoshiki; Miyoshi, Tatsuya; Mochizuki, Yasuhide; Fukuda, Yuko; Tatsumi, Kazuhiro; Matsumoto, Kensuke; Okita, Yutaka; Hirata, Ken‐ichi
Abstract : Background: Identification of heart failure (HF) symptoms in patients with severe aortic stenosis (AS) and preserved left ventricular (LV) ejection fraction (EF) is clinically important, but assessment of HF symptoms is challenging. It was recently reported that resting left atrium (LA) functions are related to exercise performance and are also important prognostic markers for patients with HF. The aim of this study was to assess the association of the HF symptoms with LA function in patients with severe AS and preserved LVEF. Methods: We retrospectively studied 40 patients with severe AS and preserved LVEF (all ≥50%) who were referred for aortic valve replacement (AVR). LA reservoir (SR‐LAs), conduit (SR‐LAe), and booster‐pump (SR‐LAa) functions were determined as the averaged global LA speckle tracking longitudinal strain rate from apical four‐ and two‐chamber views. Twenty patients were symptomatic and 20 asymptomatic. Results: Aortic stenosis severity was similar for the 2 groups. Symptomatic status was associated with age, LV mass index, hemoglobin, B‐type natriuretic peptide, LV end‐systolic volume index, LVEF, LA volume index, SR‐LAs, SR‐LAe, and SR‐LAa. Importantly, multivariate logistic regression analysis revealed that SR‐LAa was the only independent determinant of symptomatic status (OR = 0.242, P = 0.002). Furthermore, significant improvement of SR‐LAa was observed along with the reduction in LA volume index and LV mass index after AVR. Conclusions: SR‐LAa was found to be associated with the HF symptoms. Characterization of LA booster‐pump function may be useful for the assessment of the symptomatic status in patients with severe AS patients and limited physical activity.